Factors favoring the search on PubMed among Latin American medical students - Valladares Garrido, Mario Josue (2020)
Aim: To determine the factors associated with the frequent use of PubMed in medical students from 40 Latin American medical schools. Methods: We developed a cross-sectional analytical study from medical students from Latin America. The dependent variable was the frequent use of PubMed, defined as the use report at least once a week and daily. Simple and multiple regression models were constructed, estimating prevalence ratios (RP) using multilevel generalized linear models. Results: Of 11587 students, 59.3% reported using PubMed frequently. Students who belonged to clinical cycles (RP = 1.19), who were affiliated with a SOCEM (RP = 1.13), who reported mastery of basic (RP = 1.25), intermediate (RP = 1.47) and advanced (RP = 1.46), Bibliographic search training (RP = 1.22) and database training (RP = 1.42) had a higher frequency of use of this database. Conclusions: The report of frequent use of PubMed in undergraduate is high. Modifiable factors positively associated with frequent use of PubMed were the training report in bibliographic search, the report in use of the database, the report of English proficiency, and belonging to a SOCEM.